Maya E groups : calendars, astronomy, and urbanism in the early lowlands (Maya studies, 2018)
This volume assembles a coherent set of chapters that discuss new field research results on E Groups and establish an emerging paradigmatic framework for the origins of lowland Maya civilization focused on the E Group phenomenon as a key feature of community organization and urbanism in its geographic heartland.